Rancang Bangun Alat Pengupas Jengkol (Pithecellobium jiringa) Semi Mekanis - Muhammad Yasir Arafat; Tamrin Tamrin; Winda Rahmawati; Warji Warji (Jurnal Agricultural Biosystem Engineering, 2023)
Research on jengkol peeling aims to facilitate in stripping effectively, efficiently and also minimize the organs of the body namely the injured finger at the time of stripping of the jengkol fruit. Testing this tool uses 18 samples of jengkol fruit divided into 2 types namely young and old, with diameters small, medium and large. The parameters observed in this study are the performance of the jengkol peeling tool and the success of stripping. The results of this study showed that the capacity of stripping small young jengkol fruit is 540 pieces per hour and the percentage of fruit peeling success is 100%, for young jengkol medium capacity is 300 pieces per hour and the success of stripping fruit skin is 94% and for young jengkol the capacity is 300 pieces per hour and the success of stripping 94%. Meanwhile, the small old jengkol fruit is 780 pieces per hour and the success of stripping the skin is 100%, for the old jengkol is 420 pieces per hour and the success of stripping 95% and for the large old jengkol is 300 pieces per hour and the success of stripping is 100%. Keywords: Design Build, Jengkol, Skin Jengkol.